Transforming Failure into Sustainability: The Significance of Team Psychological Capital and Organizational Citizenship Behavior in Augmenting Startup Employees - Setiawan, Bambang Moertono; Soedarmadi, Yanies Novira; Irkham, Muhammad Daffa; Ulinnuhaa, M Ihkam (Integrated Journal of Business and Economics (IJBE), 2025)
The high failure rate of startups in Indonesia raises significant concerns regarding long-term sustainability as fundamental components of the digital economic development. In response to this issue, the present study explores an innovative approach by emphasizing team management as a strategic solution. Specifically, this research examines the impact of team psychological capital on team effectiveness, with a particular focus on the mediating role of organizational citizenship behavior. A total of 130 startup employees in Indonesia were selected through a purposive sampling technique. Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS) via SmartPLS 4.0 software. The empirical findings indicate that both team psychological capital and organizational citizenship behavior exert a significant and positive influence on team effectiveness. Moreover, organizational citizenship behavior is identified as a mediating variable in the relationship between team psychological capital and team effectiveness. These results underscore the crucial role of strengthening team psychological capital and fostering organizational citizenship behavior to enhance team performance. The study offers valuable theoretical and practical implications for human resource practitioners, startup founders, and managers in their efforts to optimize team dynamics and ensure the sustainability of startup enterprises